MODEL-MODEL PEMBELAJARAN (EMPAT RUMPUN MODEL PEMBELAJARAN) - Mirdad, Jamal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2020)
The learning Model is defined as a teaching plan that shows a specific pattern of learning, in which the pattern can be seen by teacher and student activities, as well as learning resources used in realizing learning conditions or systems Environment that allows students to learn. In the learning model there are characteristic sequences of teacher and student activities in the learning event known as syntax with four characteristics of learning model with curriculum. This curriculum is a guideline for the implementation of learning activities to achieve specific educational objectives through components of the curriculum change